Interactive Pick and Place Robot Control using Image Processing Method (International Journal of Engineering and Computer Science, 2014)
In this paper we describe a straight forward technique for tracking a human hand based on images acquired by an active stereo camera system. We demonstrate the implementation of this method for pick and place robot as part of a multi-modal man-machine interaction system: detecting the hand-position, the robot can interpret a human pointing gesture as the specification of a target object to grasp.